A Comparison of COVID-19 Stigma and AIDS Stigma During the COVID-19 Pandemic: A Cross-Sectional Study in China - Li, Manyun; Long, Jiang; Wang, Xuyi; Liao, Yanhui; Liu, Yueheng; Hao, Yuzhu; Wu, Qiuxia; Zhou, Yanan; Wang, Yingying; Wang, Yunfei; Wang, Qianjin; Ma, Yuejiao; et al. (Frontiers in Psychiatry, 2021)
Objective: To understand the current situation of stigmatizing attitudes towards Coronavirus Disease 2019(COVID-19) in China, and compare it with acquired immunodeficiency syndrome (AIDS).Methods: Convenient sampling and vignette-based methods were used to recruit participants on WeChat. Demographic form, adopted stigma scale were used to collect participants’ demographic information and stigmatizing attitudes towards COVID-19 and AIDS.Results: A total of 13994 questionnaires were included in this study. A high portion of participants tend to avoid contact with individuals affected with COVID-19 (74.3%) or AIDS (59.0%), as well as their family members (70.4% for COVID-19 and 47.9% for AIDS). About half of the participants agreed that affected persons could not only cause problems to their own family but also have adverse effects on others (59.6% and 55.6% for COVID-19, 56.9% and 47.0% for AIDS). The agreements with statements about perceived stigma were similar but slightly higher than personal stigma in both COVID-19 and AIDS. Participants obtainedCOVID-19 related information mainly from social media (91.3%) and newspaper or television (77.1%) during the epidemic, and 61.0% of them thought information from newspapers or television was the most reliable.Conclusion: Several similarities and differences of people’s attitude towards COVID-19 and AIDS were found. Avoidance, blame, and secondary discrimination to diagnosed person and their surrounding persons were the main representations of COVID-19 related stigma. Stigma of COVID-19 had less moral link but more public panic. Experience from HIV-related stigma reduction and prevention can be applied to reduce COVID-19 related stigma.